Teachers’ perceptions of interactive Islamic Prayer (iIP) - Farsi, Mohammed; Munro, Malcolm (Advances in Social Sciences Research Journal, 2019)
This paper explores from the teachers’ point of view how new interactive technology for teaching the Islamic Prayer in Primary Schools can enhance engagement and interaction in the classroom. An interesting aspect of the research in Human Computer Interaction (HCI) is that it focuses on both the human and computer perspectives. From the technological side, the focus is on how the computer hardware can improve the quality of HCI. Computer graphics for example, aims to ensure the graphics of a game is of a good standard so users will enjoy their game play, whilst operating systems are also considered in order to ensure good multiprocessing and to tune system response times to human interaction times. From the human side, HCI is primarily focused on the cognitive relationship with computers by ensuring the design is suitable for humans to operate successfully. The interactive Islamic Prayer (iIP) system designed for Xbox 360 Kinect with this specific goal in mind, and as an alternative to traditional learning methods. The participants for the research are Saudi Arabian primary school teachers in Jeddah, who currently teach the prayer using a traditional method. The teachers were experienced in all methods of learning (the controlled traditional method, and the iIP software) before making an informed decision on which method they prefer through a qualitative analysis of the participants teaching experiences. In addition, observations of each teaching session were organized to see how the methods engage the learners. The results show that learning by doing is extremely effective in helping the pupil’ practice, interact and remember the prayer movements.